Prinsip Pengembalaan Berdasarkan 1 Petrus 5:1-4 Dan Impilikasinya Bagi Pelayan Gembala Masa Kini - Josep Lumbantoruan; Adi Suhenra Sigiro (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The pastor is a leader for the congregation who thinks about the spirituality of the congregation and also the physical needs of the congregation he serves. Therefore, the pastor's service to the congregation is a holistic service. If the congregation served by a pastor has problems in terms of spirituality or life needs, the pastor must be willing to carry out visits and counseling. Considering that the responsibility of pastoral care is quite large, being a pastor must be a calling in life. However, it is very ironic that there are still pastors today who do not serve the congregation totally. This article is a qualitative method by examining God's servants or Shepherds as leaders. The principles of shepherding are based on 1 Peter 5:1-4, namely serving without seeking one's own interests, serving voluntarily, serving with enthusiasm and providing an example to the sheep or congregation.